In-situ characterization of chemical annealing of a-Si:H by photoelectron spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
The effect of chemical annealing with atomic hydrogen on a-Si:H samples was investigated in situ using surface sensitive spectroscopies. Changes in the hydrogen concentration and configuration as well as in the near surface defect state density are observed and are compared to the corresponding changes with deposition temperature. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.insitu